Building Trust and Collaboration: The Impact of Hybrid Leadership on Stakeholder Relations in Islamic Education - Dhuhuri, Agung Harliyadi Imam; Permana, Moch Andi; Zahroh, Ismatu; Mahfiroh, Lailatul (JURNAL AL-TANZIM, 2025)
This study examines how a principal's leadership style manages stakeholder dynamics in an Islamic elementary school. A qualitative case-study design was used with key informants (principals, teachers, foundation managers, administrative staff, and parents). Data were gathered through interviews, direct observation, and literature review, and analysed descriptively-narratively using the interactive model of Miles, Huberman, and Saldaña. Findings indicate that the principal employs a hybrid style that blends transformational, servant, and situational leadership; that spiritual values guide decision-making; that two-way communication and team empowerment are core strategies; and that flexibility is exercised to fit the context. The study identifies perceptual gaps—particularly regarding decision-making transparency, role clarity in school–foundation–parent relations, the extent of stakeholder involvement in planning, and alignment on long-term direction. Foundation backing, structured parent collaboration, and strengthened interpersonal capacities emerge as critical enablers. These findings explain why value-driven, reflective, and participatory leadership can foster a healthy, collaborative school culture: the combination of spiritually anchored decisions, open communication, participative forums, and adaptive role negotiation reduces misunderstandings, builds trust, and coordinates action. Realising holistic and sustainable Islamic education nevertheless requires tighter stakeholder synergy and continuous capacity building.